A Survey of Experimental LQR for Cart and Pole - Hoang, Dai-Phuc; Nguyen, Hoang-An; Pham, Quang-Sang; Pham, Huu-Chi; Huynh, Minh-Son; Phan, Duy-Phong; Truong, Nhut-Thanh; Nguyen, Dinh-Phat; Nguyen, Tran-Tu-Uyen; Nguyen, Hai-Thanh (Journal of Fuzzy Systems and Control, 2024)
This study explores using an LQR control for a balancing model of the inverted pendulum (IP) on a cart and pole system at the equilibrium point. The approach starts by deriving the system's motion equations by Lagrangian method. Moreover, real-world experiments are conducted to validate the proposed control strategy, demonstrating its practical applicability and robustness specifically in the context of stabilizing IP systems on carts. Thence, this model can be a standard training model for laboratory in control theory.